Seed mass maturity in the terrestrial bromeliad Hechtia perotensis (Bromeliaceae), endemic to Mexico - Elizalde, Violeta (2021)
Introduction: H. perotensis is a plant with a high potential for ecological restoration because it yields thousands of seeds and grows under low levels of rain, poor soils and contrasting temperatures. However, little is known of the seed mass maturity (high seed germination, low seed fresh weight and low seed moisture content) in this species. Objective: Assess seed germination in the laboratory of H. perotensis during seed development and along the floral stalk (infructescence) in two sites one in rocky location and another near a lake. The hypothesis was that there is a time after flowering in which seeds have highest germination and fresh weight and that the apical, centre and base of the infructescence are different in seed germination and fresh weight in both sites. Methods: Capsules were collected in two sites one in rocky land (Frijol Colorado, Perote, Veracruz) and another near one lake (Alchichica, Puebla), in the months of August, September and November 2016 and January 2017. A repeated measure design (RMD) was used to analyze the effects of infructescence section on seed weight, moisture content and seed germination (41, 87, 152 and 215 days after flowering). Each evaluation time comprised five replicates, each one with 15 seeds. Results: Difference in seed germination, seed weight and moisture content between sections of the infructescence was not significant. However, significant differences were found not only between first and last sample dates, buy mainly between first and second dates. Eighty-seven days after flower pollination seed moisture content was lower than 20 % and up to 80 % of seed germinated in both sites of sampling. Conclusions: In this study it was found that the moisture content of H. perotensis seed can be used as an indicator of the physiological maturity of the seed and it is also related to germination of the seed.